Prevalence and risk factors of urogenital schistosomiasis among under-fives in Mtama District in the Lindi region of Tanzania. - Vivian Mushi; Abdallah Zacharia; Magdalena Shao; Marycelina Mubi; Donath Tarimo (Public Library of Science (PLoS), 2022)
Introduction Despite the ongoing intervention for schistosomiasis control among school-age children in the Lindi region of Tanzania, urogenital schistosomiasis continues to be a public health problem, presumably because other at-risk populations are not covered in praziquantel deworming campaigns. Evidence shows that under-fives become infected in their early life hence the need to understand the disease profile and the risk factors for exposure to infection so as to plan effective control strategies in this group. This study examined the prevalence and risk factors of urogenital schistosomiasis among under-fives in the Mtama district, Lindi region of Tanzania. Methodology/principal findings A quantitative community-based cross-sectional study was carried out among 770 participants (385 under-fives and their 385 parents/guardians) in the Mtama district to investigate the burden and the risk factors associated with S. haematobium infection. A single urine specimen was collected from the under-fives and tested for macro and microhaematuria, presence of S. haematobium ova, and intensity of infection. A structured questionnaire gathered on risk factors for S. haematobium exposure in under-fives from their parents/guardians. Data analysis was performed using descriptive statistics, chi-square test, and logistic regression. Prevalence of S. haematobium ova was 16.9%, and that of macro and microhaematuria was 6% and 17.9%, respectively. Of the 65 positive under-fives, 49 (75.4%) 95% CI 65.4-86.3 had a light infection intensity, and 16 (24.6%) 95% CI 13.7-35.5 had a heavy infection intensity. Among the assessed risk factors, the parents/guardians habit of visiting water bodies for domestic routines (AOR: 1.44, 95% CI: 1.13-1.74), especially the river (AOR: 6.00, 95% CI: 1.20-35.12), was found to be a significant risk factor for infection of S. haematobium in under-fives. Conclusion/significance A moderate prevalence of S. haematobium was found among the under-fives conceivably with adverse health events. The infected under-fives could be a source of continuity for transmission in the community. An intervention that covers this group is necessary and should be complemented with regular screening, health education campaigns, and an adequate supply of safe water.